Perspectives on teaching and learning English Literacy in China - Ruan, Jiening; Leung, Cynthia (Dordrecht ; New York : Springer, 2012)
This comprehensive book surveys English literacy instruction in China from the first English school in the 19th century to recent moves to modernize English instruction. Covers early childhood education, teaching English to Chinese minority students and more.
Social Ideologies and the English Curriculum in China: A Historical Overview / Ran Hu, Bob Adamson -- English Language Teaching in Higher Education in China: A Historical and Social Overview / An Cheng, Qiuying Wang -- English Curriculum and Assessment for Basic Education in China / Yongqi Gu -- Early Childhood English Education in China / Zhenyou Yu, Jiening Ruan -- Chinese Primary School English Curriculum Reform / Dongbo Zhang -- Twenty-First Century Senior High School English Curriculum Reform in China / Qiang Wang, Zehang Chen -- English Curriculum in Higher Education in China for Non-English Majors / Meihua Li -- After School English Language Learning in China / Ping Liu -- English Teaching and Learning in Ethnic Minority Regions in China: Challenges and Opportunities / Anwei Feng -- Use of Technology to Support the Learning and Teaching of English in China / Guofang Li, Xiaopeng Ni.
Includes bibliographical references and index.
Keywords: English language -- Study and teaching -- China